Liver Transplantation in Alcohol-Associated Hepatitis. Benefits and Limitations of Psychosocial Selection and Support in Alcohol Relapse. The Experience of a Tertiary Center in Italy - Luca S. Belli; Adelaide Panariello; Giovanni Perricone; Paola Prandoni; Raffaella Viganò; Chiara Mazzarelli; Chiara Becchetti; Sara Giacalone; Giovanna Donvito; Sara Conti; Paolo A. Cortesi; Elena Roselli; et al. (Transplant International)
Patients with severe alcoholic hepatitis SAH may suffer of undiagnosed psychiatric illnesses, typically depression. Assessment of prevalence and potential impact of psychiatric disturbances on alcohol relapse after LT, were the main objectives of this study. One hundred consecutive patients with SAH from April 2016 to May 2023 were analyzed. All patients were evaluated by an integrated team including psychiatrists, addiction specialists and social workers. Thirty (30%) were listed, of whom 25 underwent early liver transplantation (eLT) after a median time of 36 days from the index episode of SAH with a median model for end stage liver disease (MELD) score of 36, whereas 33 (33%) were excluded, with psycho-social issues being the main cause of exclusion in 18 patients (54.5%). Twenty-four patients (96%) are currently alive after a median follow-up of 32 months from LT. Sixteen transplanted patients had major depression with or without anxiety, with 10 patients (33%) being treated with antidepressants post-LT. Overall, 4 patients (16%) relapsed into alcohol consumption after liver transplantation and 1 died of alcohol related liver disease (4%). From this experience emerged that psychiatric comorbidities are highly prevalent among patients with SAH and that their diagnosis/treatment contributed to mitigate the risk of alcohol relapse.